B-1 cells contribute to increased total IgM and shape IgG autoreactivity profiles in Lyn-/- mice but are not a major source of lupus-associated pathogenic autoantibodies - Ottens, Kristina; Satterthwaite, Anne B. (Frontiers in Immunology, 2025)
IntroductionSystemic lupus erythematosus is an autoimmune disease in which pathogenic autoantibodies targeting nucleic acid containing antigens promote inflammation and tissue damage. Recent reports suggest that deep B cell depletion will be a highly effective therapeutic strategy for lupus. However, elimination of all B cells confers susceptibility to infection. Thus, an approach which targets pathogenic B cells but spares protective ones would be ideal. The B-1 subset of B cells has been suggested to be either pathogenic or protective in lupus, depending on the study.MethodsWe used several complementary approaches to define the contribution of B-1 cells to autoantibody production and immune cell activation in the Lyn-/- mouse model of lupus. We labeled activated B-1 cells to track their cellular and antibody progeny. Activated B-1 cells were also depleted or prevented from differentiating into plasma cells.ResultsB-1 cells contributed significantly to the accumulation of splenic plasma cells and total IgM characteristic of Lyn-/- mice in a manner at least partially independent of the transcription factor IRF4. Unlike T-bet+ B cells, they were not a major source of pathogenic lupus-associated autoantibodies. Rather, they limited both the production of IgG against other autoantigens and the activation of CD8+ T cells.ConclusionThese studies highlight a regulatory role for B-1 cells in shaping adaptive immune tolerance in the Lyn-/- lupus model.